2018
DOI: 10.1002/mdc3.12662
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Rituximab Response on Tremor Related to Acute‐Onset Chronic Inflammatory Demyelinating Polyradiculoneuropathy in an Antineurofascin155 Immunoglobulin G4–Seropositive Patient

Abstract: View Supplementary Video 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…CIDP associated with IgG4 anti-CNTN1 antibodies have a more frequent acute or subacute onset than those associated with IgG4 anti-Nfasc155. Postural tremor was present in 4/10 of our patients and reported in 3/4 patients in a previous study [12], but this seems less disabling than that reported in CIDP associated with IgG4 anti-Nfasc155 [22,23]. Our patients with anti-CNTN1 antibodies had frequent bifacial palsy.…”
Section: Discussionsupporting
confidence: 43%
“…CIDP associated with IgG4 anti-CNTN1 antibodies have a more frequent acute or subacute onset than those associated with IgG4 anti-Nfasc155. Postural tremor was present in 4/10 of our patients and reported in 3/4 patients in a previous study [12], but this seems less disabling than that reported in CIDP associated with IgG4 anti-Nfasc155 [22,23]. Our patients with anti-CNTN1 antibodies had frequent bifacial palsy.…”
Section: Discussionsupporting
confidence: 43%
“…Rituximab has previously been suggested as an effective treatment for paranodal antibody positive patients [42,43], but may take several weeks (or even months) to produce benefit. In this case, a second cycle of IA, 4 weeks after a course of rituximab, produced a more persistent suppression of antibody titres, which was associated with clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The weakness was mild to moderate and predominantly localized at distal sites. Recent reports have described additional features, such as head and tongue tremors 33‐35 . Laboratory findings showed that antibody‐positive patients had remarkably high CSF protein levels, usually >200 mg/dL, whereas seronegative patients commonly had levels <100 mg/dL 22,36 .…”
Section: Clinical Features Of Patients With Antibodies Against Node Omentioning
confidence: 99%